2021
DOI: 10.1002/cfp2.1132
|View full text |Cite
|
Sign up to set email alerts
|

Emerging adulthood milestones, perceived capability, and psychological well‐being while transitioning to adulthood: Evidence from a national study

Abstract: Using the 2017 wave of the transition to adulthood dataset, this study examined the association between the achievement of key milestone markers of adulthood and the well-being of emerging adults between ages 18 and 28. Results indicate that relationship status, financial behavior, and perceived capability were positively associated with the well-being of emerging adults. The results also indicate that financial responsibility, mediated by cohabiting relationship status, was negatively associated with relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…If the association is unable to utilize financial literacy, then its financial well-being cannot be improved. Fourthly, this model was created to demonstrate the relationships involving financial literacy, socioeconomic status, and financial well-being, particularly among B40 households, Chatterjee et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…If the association is unable to utilize financial literacy, then its financial well-being cannot be improved. Fourthly, this model was created to demonstrate the relationships involving financial literacy, socioeconomic status, and financial well-being, particularly among B40 households, Chatterjee et al [37].…”
Section: Discussionmentioning
confidence: 99%
“…In a different perspective on the issue of young adults' financial strain, Chatterjee et al (2021) [ 23 ] found that dissatisfaction with current non-marital relationship would mediate the association between financial strain and psychological well-being of emerging adults. On the other hand, Falconier and Jackson (2020) [ 24 ] demonstrated that financial strain had negative effects on relationship stability and satisfaction as well as on one's physical and mental health.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Responsibility refers to the development of personal and social responsibilities, such as self-care and social contribution [2,6]. Accepting responsibility is associated with perceived emotional well-being and life satisfaction in emerging adults [15]. Therefore, positively improving the characteristics of these adults is very important to promote their physical and mental health.…”
Section: Introductionmentioning
confidence: 99%